Effect of Mantha langifoliail (L)powder inhabit growth of fungi that associated with local bread - Merjan, Ali Merjan (University of Thi-Qar Journal of agricultural research, 2026)
Contamination local bread wit mold were tested to identifying fungi and verifying efficiency of Mantha langifoliail (mint) ti inhibet fungi contamination and longing life half of bread product